Effects of One Versus Two Doses of a Multi-Ingredient Pre-Workout Supplement on Metabolic Factors and Perceived Exertion during Moderate-Intensity Running in Females - Jamie R. Erickson; Clayton L. Camic; Andrew R. Jagim; Paige M. Pellersels; Glenn A. Wright; Shaine E. Henert; Carl Foster (MDPI AG, 2020)
The primary purpose of this study was to examine the acute effects of one versus two doses of a multi-ingredient pre-workout supplement on energy expenditure during moderate-intensity treadmill running. In addition, our second aim was to investigate the responses of associated metabolic factors (i.e., substrate utilization, measures of gas exchange), perceived exertion, and resting cardiovascular variables with one and two doses of the pre-workout supplement. Twelve females (mean ± SD: age = 25.3 ± 9.4 years; body mass = 61.2 ± 6.8 kg) completed three bouts of 30 min of treadmill running at 90% of their ventilatory threshold on separate days after consuming one dose of the pre-workout supplement (1-dose), two doses (2-dose), and a placebo. There were no differences among conditions for energy expenditure, fat or carbohydrate oxidation, respiratory exchange ratio, oxygen consumption, or heart rate across exercise time. The two-dose group, however, had lower (p = 0.036) ratings of perceived exertion (11.8 ± 1.7) than the one-dose (12.6 ± 1.7) and the placebo (12.3 ± 1.2) at the 20-min time point of exercise as well as greater resting systolic blood pressure (110 ± 10 mmHg) compared to the one-dose (106 ± 10 mmHg) and the placebo (104 ± 10 mmHg) conditions. Both the one-dose and two-dose conditions had greater increases in diastolic blood pressure compared to the placebo. Thus, our findings indicated that the present pre-workout supplement had no performance-enhancing benefits related to energy metabolism but did attenuate feelings of exertion.